A Challenging Diagnosis of IgG4-Related Disease When Understanding Limitations of Laboratory Testing Was Pivotal. (30th July 2017) - Xu, Victoria Y. Y.; Bell, Mary; Zahirieh, Alireza; Hsiao, Janey; Higgins, Kevin; Ghorab, Zeina; Bookman, Arthur; Chan, Pak Cheung
Abstract : A 76-year-old man was incidentally found on a CT scan to have lymphadenopathy and bilateral kidney enlargement suggestive of infiltrative renal disease. He was largely asymptomatic but had bilateral salivary and lacrimal gland enlargement. A grossly elevated serum IgG (>70 g/L) with concomitant suppression of other immunoglobulins, a small IgG restriction, and a parotid biopsy revealing lymphoplasmacytic infiltrate with slight kappa light chain excess all suggested a lymphoproliferative disorder (LPD). The diagnostic workup was further confounded by a normal serum IgG4 concentration. Moreover, bone marrow and renal biopsies did not reveal evidence of LPD. Discussion with the laboratory not only clarified that the markedly increased total IgG could not be accounted for by the small IgG restriction, but also identified a discrepancy in the IgG4 measurement. Repeat analysis of a follow-up sample revealed an elevated IgG4 of 5.94 (reference interval: 0.039–0.864) g/L, which prompted a repeat parotid biopsy that showed predominant IgG4+ lymphocytic infiltrates. Despite the deluding presentations, a final diagnosis of IgG4-related disease (IgG4-RD) was made based on elevated serum IgG4 concentrations and histopathological findings. This case highlights the importance of recognizing limitations of laboratory testing and the benefit of close communications among clinical subspecialties and the laboratory.